(untitled) (Bangladesh Journal of Zoology, 2021)
Rapid urbanization is changing the habitats of many wildlife species. Even so, certain species appear to adapt and now have thriving populations within cities. To look at the capacity for these spaces to provide “habitat” we examined population density of bird species using Jahangirnagar University campus close to the Dhaka mega city, Bangladesh. Four strip transects were surveyed from March 2008 to February 2009 (12 times/transect). A total of 101 species were found along the transect areas. The density of Lesser Whistling Duck (Dendrocygna javanica) was the highest 107.02indiv. /ha while Large-tailed Nightjar (Caprimulgus macrurus) was the lowest 0.01indiv. /ha among resident birds of Jahangirnagar University campus. Among the migratory birds, the density of Pintail Snipe (Gallinago stenura) and Common Stonechat (Saxicola torquata) were the highest (1.99indiv. /ha.) and the lowest (0.02indiv. /ha.), of the different available habitats, water bodies contained the highest density (318.59indiv. /ha) and grassland contained the lowest (2.48indiv./ha) of bird population. The percentage of average density of non-passerine and passerine birds was 65% and 35%, respectively. Future studies of avian composition and density is recommended at a regular interval to understand changes in the carrying capacity and avian community of the campus as a function of altering habitat due urbanization. Bangladesh J. Zool. 48(2): 289-300, 2020